2015
DOI: 10.1089/env.2015.0011
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Availability of Farmers Markets in the United States

Abstract: Farmers markets (FM) have been proposed by researchers, policymakers, and health agencies as a potential community-level strategy to prevent obesity and reduce disparities in healthy food access in the U.S. Information about disparities in farmers market availability is scarce. This research aimed to examine county-level associations between farmers market (FM) availability and demographic, socioeconomic, health, and environmental measures in an effort to determine if disparities in availability exist in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
(39 reference statements)
2
12
0
Order By: Relevance
“…However, for these initiatives to develop, stakeholders pointed toward three main issues that must be addressed: physical accessibility, affordability, and accessibility to knowledge with regard to good nutritional practices and the preparation of meals from fresh products. Incidentally, these same issues have likewise been identified in the literature (Colasanti et al, 2010;Singleton et al, 2015).…”
Section: The Welfare Of the Communitysupporting
confidence: 53%
“…However, for these initiatives to develop, stakeholders pointed toward three main issues that must be addressed: physical accessibility, affordability, and accessibility to knowledge with regard to good nutritional practices and the preparation of meals from fresh products. Incidentally, these same issues have likewise been identified in the literature (Colasanti et al, 2010;Singleton et al, 2015).…”
Section: The Welfare Of the Communitysupporting
confidence: 53%
“…The number of fruit and vegetable wholesalers is only weakly associated with the probability of observing a positive number of FMs. The estimated coefficients for the number of grocery stores indicates a positive and decreasing relationship with participation, suggesting that grocery stores and FMs may be complementary shopping experiences (consistent with Morgan and Alipoe 2001, and Singleton, Sen, and Affuso 2015). This could be indicative of demand for similar services or co-location strategies where both types of outlets try to locate in areas with larger demand.…”
Section: Resultssupporting
confidence: 60%
“…On the one hand, grocery stores may compete with FMs as a substitute, leading to lower profit margins for farmers participating in FMs and consequently a lower probability of FMs being established. On the other hand, previous research has shown grocery stores may complement FMs, therefore showing a positive association with FMs (Morgan and Alipoe 2001, Singleton, Sen, and Affuso 2015).…”
Section: Datamentioning
confidence: 89%
See 1 more Smart Citation
“…Other barriers include the geographic location of the markets and market open times. Farmers markets are most commonly positioned in affluent, white areas (Singleton, Sen, & Affuso, 2015), and potential low-income participants experience a range of access barriers, includ-ing lack of time and inadequate transportation (Walker, Keane, & Burke, 2010). Local foods are also limited by season and are more labor intensive to locate and prepare; thus, they may be perceived as an impractical food solution for many potential consumers (Leone et al, 2012).…”
Section: Introductionmentioning
confidence: 99%